2015
DOI: 10.15414/jmbfs.2015.4.special1.16-18
|View full text |Cite
|
Sign up to set email alerts
|

Microfungi and Mycotoxins of Grapes From Tokaj Wine Region

Abstract: The aim of this study was to investigate a surface mycobiota of grapes and detection a potentially pathogenic isolates to produce selected mycotoxins. Three samples of wine grapes Furmint, Lipovina and Yellow muscat were collected in the Tokaj wine region in Viničky during the November harvest in 2012. Seven/eight berries from each sample were placed on a Dichloran Rose Bengal Chloramphenicol agar in a total of 50 and incubated at 25 °C for 5 - 7 days. After incubation from the samples were isolated following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Particularly, several cases of penitrems-associated poisonings were linked to the consumption of contaminated rice, beans, and tomatoes [ 47 ]. In addition, Pen A was found to be a contaminant of wine [ 48 ]. Rice, white beans, tomatoes as well as green and red grape were inoculated with P. crustosum and incubated for two weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, several cases of penitrems-associated poisonings were linked to the consumption of contaminated rice, beans, and tomatoes [ 47 ]. In addition, Pen A was found to be a contaminant of wine [ 48 ]. Rice, white beans, tomatoes as well as green and red grape were inoculated with P. crustosum and incubated for two weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the color of fungi or the spores is not directly related to toxin production. Fungal species can vary widely in color, and while some toxigenic fungi may have characteristic colors, it is not a reliable indicator of toxin production [22,23]. The ability of a fungus to produce toxins depends on various factors such as species, environmental conditions, and genetic makeup.…”
Section: Discussionmentioning
confidence: 99%
“…However, the distortion of the berries surface by one fungus can favor the berries colonization by others-e.g., pathogenic black Aspergilli. The presence of Aspergillus and Penicillium fungi as potential producers of mycotoxins on botrytized berries in the Tokaj wine region has already been confirmed [12,13]. In addition, Gil-Sena et al reported the more frequent OTA contamination of sweet wines [14].…”
Section: Introductionmentioning
confidence: 90%